(untitled) (Journal of Hama University, 2020)
The problem of cleftlip remains an urgent issue in plastic reconstructive oral and maxillofacial surgery because there is no ideal way to end all existing problems with these clefts in terms of symmetry, psychological , rehabilitation of the patient and his involvement in society and function. The aim of this research was to evaluate the results of oral and nasal symmetry after the primary repair of unilateral cleftlip when following the Millard technique and the modification of Asensio .The research sample consisted of 20 cases suffering from unilateral cleftlip ( complete and incomplete ) , and their ages ranged between 3-6 months .The sample was divided into two main groups : A first group consisting of 10 cases , on which Millard technique was applied during the primary repair , and a second group consisting of 10 cases on which the Asensio technique was applied .Cases were observed after 15 days and 6 months of surgery to assess oral and nasal symmetry by clinical photographs only .Arithmetic averages for all studied variables for both methods followed after 15 days of surgery did not show any statistical differences due to the level of significance is greater than 0,05 .While … These averages showed calculated changes after 6 months of surgery in favor of the Asensio method for oral and nasal symmetry and therefor it is advised to use this method to repair complete and incomplete unilateral cleftlip as an alternative to Millard technique .